2022
DOI: 10.3390/medicina58070863
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Suicidal Thoughts in Breast Cancer Patients

Abstract: Background and Objectives: Women diagnosed with breast cancer experience severe trauma. Psychological help for breast cancer patients is not sufficient because of limited professional resources. The goal of this study was to identify groups of breast cancer patients with the greatest suicidal risk, who could be the first target for psychosocial interventions. Materials and Methods: The study included 421 women with stage T1–T3/N0–N3/M0 breast cancer. We provided women with a set of questionnaires 1–2 days prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Another limitation of the present study is the non-inclusion of outcomes related to quality of life, given the recognized psychological effects of common screening outcomes such as false-positive results [ 46 ] and the overdiagnosis of breast cancer [ 23 ]. Although deaths by suicide associated with overdiagnosis were considered in the study, less extreme cases, such as depression, anxiety and posttraumatic stress disorder, are more prevalent and may be persistent [ 64 ]. Non-lethal adverse effects of overtreatment were also not considered in the present study, such as radiotherapy-induced acute dermatitis, which is common but generally of moderate intensity [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the present study is the non-inclusion of outcomes related to quality of life, given the recognized psychological effects of common screening outcomes such as false-positive results [ 46 ] and the overdiagnosis of breast cancer [ 23 ]. Although deaths by suicide associated with overdiagnosis were considered in the study, less extreme cases, such as depression, anxiety and posttraumatic stress disorder, are more prevalent and may be persistent [ 64 ]. Non-lethal adverse effects of overtreatment were also not considered in the present study, such as radiotherapy-induced acute dermatitis, which is common but generally of moderate intensity [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further programs would aim to include more men, making such programs more attractive to them, and they could be among the priorities for suicide prevention [39]. Also, research data show that cancer patients are at increased risk of suicide, and the needs in this broad field are not adequately addressed [28,[40][41][42]. In addition, research findings have demonstrated that pets and animal-assisted therapy could be beneficial in suicide prevention; the bonds between humans and animals can provide a relaxing experience, decrease psychological pain, and increase the sense of purpose and engagement [43].…”
Section: Discussionmentioning
confidence: 99%
“…En ese sentido, se encontraron diversas variables psicosociales asociadas al riesgo suicida. De relación directa, la más reiterativa fue la depresión (Kazlauskiene et al, 2022), debido a que conlleva a un déficit en la percepción y decodificación de los estímulos emocionales y los estados mentales (Khosravi & Hassani, 2022), lo que ocasiona apatía en el individuo y genera inactividad prolongada y conductas suicidas (Xiao et al, 2022). Por tal motivo, se precisa que la depresión hace que las personas se sientan aisladas e ineficientes (Anbesaw et al, 2021), dando apertura a las emociones negativas, lo cual empeora el estado de ánimo y genera un mayor riesgo suicida (Guo et al, 2021).…”
Section: Discussionunclassified